Pengembangan Bahan Ajar Matematika Berbasis Realistic Mathematic Education untuk Melatih Kemampuan Koneksi Matematika Siswa Kelas IV SDN Bengkulu Utara - Monica Ayesha Guretno; Victoria karjiyati; Pebrian Tarmizi (Universitas Bengkulu, 2022)
This study aims to produce mathematics teaching materials using the Realistic Mathematics Education (RME) approach to train the mathematical connection skills to fourth grade elementary school students. This research is a Research and Development (R&D) research by modifying the ADDIE model. This research was only carried out at the development stage, while the implementation and evaluation stages could not be carried out due to the COVID-19 pandemic. Validation is carried out by material, linguists and product design experts. The teaching materials developed were graded and responded by 3 teachers from public elementary schools in North Bengkulu. The data analysis technique used descriptive statistical analysis on the results of expert validation assessments and teacher responses and qualitative descriptive analysis on comments from expert validation and teacher responses. This research produces a product of teaching materials based on Realistic Mathematics Education (RME) to train students' mathematical connection skills in the material of measuring angles in grade IV Elementary School. This research produces teaching material products with an average material expert validation assessment of 90 with a very good category, an average linguist validation of 88.88 in a very good category, an average product design expert validation of 96.67 with a very good category. good, and get a response that the depth of the material description uses a real context according to the level of student development, in terms of the language in the teaching materials according to the level of development of the student's age, the overall illustrations and letters used are simple (communicative), harmonious and create an attraction for students to learn RME based math module. The teacher's response got an average score of 90.67 with a very good category. So it can be concluded that the product of developing mathematics teaching materials based on Realistic Mathematics Education is very good to be used by fourth grade elementary school students.Keywords: Teaching Materials, Development, Realistic Mathematics Education, Mathematics connection.